A peregrináció forgandó: A kései peregrináció arányai és árnyai – a sárospataki példa - Ugrai, János (Gerundium, 2017)
Unpredictable Peregrinations. Rates and Figures of Late Peregrination at the Reformed College of Sárospatak. Between 1781 and 1857 two third of the professors and approximately half of the junior lecturers at the Reformed College of Sárospatak left for foreign universities and colleges. Instead of the Netherlands, by the 19th century the most preferred destinations of these 1–3-year-long study trips were more accessible German universities. It was the sign of a new era that the most renowned professors of the Reformed College were those who stayed away from these peregrinations and traditional ways, and many of whom became members of the Hungarian Academy of Sciences. Interestingly, major curricular reforms and endeavours in the reform period may also be linked to such figures, including János Erdélyi, Sándor Kövy, István Nyíry and Antal Pálkövi. Comparing the life of the two professors with the longest and most successful peregrinations, we may come to completely contrasting results: while the great success of Pál Beregszászi Nagy’s peregrinations led to a rapid failure, Gábor Őri Fülep’s career took off after his long stay abroad.